The Danger of a Single Theory: Understanding Students' Voices and Social Justice in the Peruvian Andes. Issue 2 (February 2018) - Levitan, Joseph
Background/Context: Working towards social justice in education requires students' voices to be heard and understood. This is especially the case for students from marginalized populations. Prior research has shown the value and importance of students' voices for school retention, academic success, school inclusivity, and student buy-in. However, more research is needed on how adults understand and interpret students' voices and implement their understandings in school practice and policy. Purpose/Objective: This paper uncovers the danger of misinterpreting students' voices due to assumptions about concepts such as success and social justice. I explore this issue by interpreting first-generation Quechua (indigenous) students' voices about success in the Peruvian Andes through four different paradigms concerned with social change, social reproduction, and social justice. The discussion places into dialogue feminist theory, critical theory, postcolonial theory, and development theory in order to highlight the implications of each interpretive framework for responsive education policy. I show how interpretations based on each theory offer divergent school policy options, the danger of a single theory for interpreting student voice. Participants: The coresearchers for this paper are 14 young women from Quechua communities who are the first in their families to attend secondary school. Working with them are a woman from a Quechua community, a woman from Central Europe, and a man from the United States. Research Design: A collaborative ethnographic case study utilizing student voice methods. The students developed the theme and topic for research during a student-led seminar. Based on the students' questions, the adults helped facilitate the creation of an interview protocol with the students. The group answered the questions on the protocol and used the protocol to interview the students' parents. We held three total focus group discussions to develop the protocol, discuss findings, and interrogate ideas of success. Conclusions/Recommendations: The results highlight the vastly different interpretations and policy implications of students' voices based on each theory—highlighting how social justice is a complex concept that requires discussion across theoretical orientations. The findings also show points of overall congruence, and cross-theory trends. Recommendations are for educational leaders and researchers (teachers, parents, administrators) to refect and think about empirical information from multiple theoretical frameworks in order to become more aware of the influence of one's own assumptions in educational decision-making.